Program Evaluation Development in the Newly Independent States - Afar Karimov; Alexander Borovykh; Alexey Kuzmin; Asel Abdykadyrova; Djahangir Efendiev; Ekaterina Greshnova; Elena Konovalova; Inessa Frants; Liubov Palivoda; Seymour Usifli; Vladimir Balakirev (The Evaluation Center at Western Michigan University, 2007)
This paper provides a general overview of the development of program evaluation in CIS countries. We start by telling a story that describes how evaluation appeared in the scene, how it developed and who the key players were in its development. We discuss the issue of demand for and supply of evaluation services. In the conclusion, we describe our view of the stages in the emergence of evaluation in the CIS and the perspective of each. The four stages we identify are: "An External Phenomenon" (1991-1995), "Initiation" (1996-2000), "Assimilation" (2000-2004), and "Implementation" (2005 to the present).